A regional composite indicator for analysing agricultural sustainability in Portugal: A goal programming approach - Xavier, António (2018)
Sustainability in agriculture can be analysed using different types of indicators, but its quantification and aggregation into an index is still difficult. This paper proposes an approach based on goal programming to analyse sustainability at a regional level and generate a composite indicator. This approach uses several procedures in two main steps. In the first step, the weights of criteria are assigned based on the preferences of experts. In the second step, a binary extended goal programming (EGP) approach is applied to define the rankings of sustainability based on the composite indicator generated. This procedure is refined with the use of an entropy approach that overcomes difficulties already experienced by other authors. The results show that the proposed approach is an effective tool to generate composite indicators and provides an easy definition of several regional rankings of farm’s sustainability at municipality level.